(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: In biological system, cells are considered as dynamic and complex structures likewise cellulardisintegration is also a complex process which occurs in a sequence. Therefore, these autolytic cellularchanges have been investigated by forensic pathologist in an attempt to find markers that may assist indetermining the time of death. In this study we attempt to analyse the efficacy of oral soft tissues specificallysalivary gland in concluding the time since death.Methodology: After obtaining approval from the human ethical committee, informed consent from therelative of the corpse and the investigating police officer, demographic information, as well as post mortemnumber was recorded. Submandibular Salivary Gland was collected for histopathological analysis duringroutine autopsy procedure. The specimens were fixed immediately in 10% formalin, processed, sectionedand stained with haematoxylin and eosin. The stained sections were evaluated under light microscope forhistopathological changes.Conclusion. The histopathological changes in the autopsied salivary gland tissue can be used as an adjuvantto estimate the post-mortem interval.